2012
DOI: 10.1103/physrevb.85.155143
|View full text |Cite
|
Sign up to set email alerts
|

Ab initioabsorption spectrum of NiO combining molecular dynamics with the embedded cluster approach in a discrete reaction field

Abstract: We developed a procedure that combines three complementary computational methodologies to improve the theoretical description of the electronic structure of nickel oxide. The starting point is a Car-Parrinello molecular dynamics simulation to incorporate vibrorotational degrees of freedom into the material model. By means of complete active space self-consistent field second-order perturbation theory (CASPT2) calculations on embedded clusters extracted from the resulting trajectory, we describe localized spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 111 publications
3
43
0
Order By: Relevance
“…[1][2][3]31 The value of E g,ZnO in the RS structure which is reported in the literature is 2.45 ± 0.15 eV, measured by performing pressure dependent absorption measurements on ZnO thin films. The value of E g,NiO in the RS structure is 3.85 ± 0.03 eV as determined in the present study, which is in good agreement with the values reported in the literature.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…[1][2][3]31 The value of E g,ZnO in the RS structure which is reported in the literature is 2.45 ± 0.15 eV, measured by performing pressure dependent absorption measurements on ZnO thin films. The value of E g,NiO in the RS structure is 3.85 ± 0.03 eV as determined in the present study, which is in good agreement with the values reported in the literature.…”
Section: Resultsmentioning
confidence: 93%
“…4,31 The leading absorption edge observed in NiO is related to the ligand to metal charge transfer (ligand O-2p to metal Ni-3d orbitals), which is termed as the optical gap. Thus, a plot between [F(R ∞ ) × hν] n versus hν yields a straight line and the intercept on the energy axis gives the value of the bandgap.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain a clear picture on crystal-field effects and spin-orbit interactions at the central Ir site, we cutoff the magnetic couplings with the adjacent Ir ions by replacing the tetravalent open-shell d 5 NNs with tetravalent closed-shell Pt 4+ species. This is a usual procedure in quantum chemistry studies on TM systems, see for example, refs 42 , 45 , 53 , 54 , 55 , 56 . We used energy-consistent relativistic pseudopotentials and valence basis sets of quadruple-zeta quality supplemented with f polarization functions for the central Ir ion 57 and all-electron triple-zeta basis sets for the six adjacent ligands 58 .…”
Section: Methodsmentioning
confidence: 99%
“…NiO cannot trap photogenerated electrons because the conduction band of NiO is more negative than that of TiO 2 . There is some controversy in the literature about the valence and conduction band energies of NiO . Values in the ranges of −0.3 to −1.0 eV are reported for the conduction band, and 2.4 to 4.3 eV for the valence band (with respect to the standard hydrogen electrode (SHE)) .…”
Section: Introductionmentioning
confidence: 99%